Nutrition and COVID-19: an investigation of nutritional aspects and their importance in health in the view of the pandemic (Research, Society and Development, 2021)
In front of the pandemic caused by COVID-19, the whole world was seen with a new reality of uncertainty, fear, and difficulties. This new lifestyle in front of social isolation and quarantine led to behavioral changes with damage to physical and mental health. It is known of the importance of a regulated immune system as a barrier against infections that can attack our body, and that food is one of the main ways to acquire nutrients necessary for this regulation of immunity. Therefore, this work sought to investigate the influence of nutritional aspects and your importance for health in confronting with COVID-19 pandemic. Scientific articles published between the years 2019 to 2021 were selected. In these studies, it was possible to analyze and emphasize the importance of micronutrients that, inadequacy in the body or therapy with high dosages, improve the inflammation of the disease and, consequently, the prognosis of patients. Turn up the importance of further studies evaluating therapies used micronutrients in COVID-19 treatment.